Development of the ASEAN Studies Course in the Foreign Language (English) Learning Area of School-Based Curriculum for Upper Secondary Students in World Class Standard Schools - Kratoknok, Jutarat; Jearakul, Praphon; Yiemkuntitavorn, Sita; Naknaka, Poonsap Naknaka (Ratchaphruek Journal, 2019)
All schools in the World Class Standard School Project must implement their school-based curriculum a part of which includes the ASEAN curriculum. This research is conducted with the following objectives: (1) to develop the ASEAN Studies Course in the Foreign Language (English) Learning Area of school-based curriculum for upper secondary students in World Class Standard schools; and (2) to study try-out effects of the developed ASEAN Studies Course. The research sample consisted of 2 classes of upper secondary students in Sura Nari Witthaya School in Nakhon Ratchasima province, obtained by multi-stage sampling. The research instruments were (1) the developed ASEAN Studies Course; (2) a manual for conducting the course; (3) reading materials for the Course; (4) an achievement test of knowledge on ASEAN community and member countries; and (5) a questionnaire on attitudes toward studying the ASEAN Studies Course, ASEAN Community, and ASEAN member countries. Statistics for data analysis were the frequency, percentage, mean, standard deviation, and t-test. Research findings were as follows: the developed ASEAN Studies Course was a supplementary course for upper secondary students in World Class Standard schools. It could be offered at Mathayom Suksa V either in the first semester or the second semester, the developed reading materials for the course comprised 12 chapters, ten of which were on individual ASEAN member countries the first chapter was the introduction of ASEAN community, and the last chapter was the conclusion. The try-out results of the course showed that (1) the post-learning achievement of the students was significantly higher than their pre-learning counterpart achievement; and (2) the students’ attitudes toward the Course, toward ASEAN community, and toward ASEAN member countries were at the high level.